The Effect of Field Practice Lectures on Learning Motivation and Academic Ability Development of Educational Management Students - Dwi Kurnianing Ratri; Achmad Supriyanto (International Journal of Social Learning (IJSL), 2026)
The unemployment rate among university alumni in Indonesia is 5.2%. The reason is misalignment between universities and industry. MP UM offers FPL to minimize misalignment and educate on unemployment. The success of FPL is determined by learning motivation and academic development. The purpose of this study was to determine the level of FPL teaching, learning motivation, and academic development, to find the effect of FPL teaching on learning motivation and academic development, and to find the effect of FPL teaching on academic development through learning motivation. The research used a quantitative, descriptive, correlational approach. 109 students were involved through saturated samples. SPSS and SmartPLS3 were used for data analyzing. The results showed that FPL teaching, learning motivation, and academic development were very high. The evaluation process and learning reflection influence motivation and academic development. There was no direct or indirect influence of planning and implementation on motivation and academic development.